Evaluation of The Nervous System Interactive Module Based on Acceptance and Increasing Knowledge Level (Nusantara Science and Technology Proceedings, 2022)
The use of interactive nervous system modules is expected to be suitable to increase knowledge and facilitate independent learning. The interactive module used must be tested for usability. Usability and user experience are the main determinants of the quality of a product in the form of media or systems, as well as an indicator of success or failure. The purpose of this study was to evaluate the use of an interactive nervous system module that was developed based on user acceptance and increased usage knowledge. A pre-experimental one group pre–test–post–test design with a sequential explanatory mixed method was taken. The sample of this study was all participants taking the comprehensive stage in March 2022. The quantitative measurement used the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ), while the knowledge measurement used two packages of pretest and posttest questions. Further, the Qualitative measurements were carried out by interviewing to find out the advantages and disadvantages of the interactive modules that have been developed as well. There is evidence that the module increases the participant's knowledge (p-value was 0.000 using paired sample t-test). The average results of the pre-test and post-test scores were 68.33 and 83.06 respectively. The results of the measurement of user acceptance using SUS obtained a value of 73.125 which indicates that the interactive nervous system module is "Acceptable" based on acceptability ranges, "good" based on the adjective rating, and grade C based on the Grade Scale. UEQ measurement results obtained Overall “Excellent”, Pragmatic Quality “Excellent”, Hedonic Quality“Excellent”. The participants of the Comprehensive Stage said that the interactive nervous system module had advantages in terms of the system, easy access, attractive appearance and easy to understand. The drawback is that the use on mobile devices is still less comfortable when compared to use on laptops and tablets. Our study concludes that the use of these interactive nervous system modules is well acceptable as it can facilitate students' independent learning and increase knowledge. Moreover, Interactive modules also have advantages in terms of systems, ease of access, attractiveness and clarity of material, however the improvement in appearance to keep comfortable when user use on mobile devices is still needed.